IMR 665: Management of Audio Visual Records & Archives. Individual Assignment: Article summary / Izwan Hairuddin Sabri - Sabri, Izwan Hairuddin (2015)
Article summary: “2012 Survey of the Preservation, Management, and Use of Audiovisual Media in European Higher Education Institutions” & “The Conservation and Preservation of Film and Magnetic Materials (2): Magnetic Materials”